PERLINDUNGAN PEMILIK MEREK DAGANG EIK YANG DIGUNAKAN DI INDONESIA MELALUI PERJANJIAN DISTRIBUTOR (ANALISIS PUTUSAN NOMOR 1300 K/Pdt.SUs_HKI/2017) - Simona Bustani; Theodorus Felix Wangsa (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
It is still a debate about the controversy of brand protection systems in Indonesia regarding systems first to file. The distributor agreement was also seen to be a gap for principals who did not understand the system first to file. What protection is given to brand owners? Problem research uses normative research with an approach to law and cases. The data used is secondary data. Protection for brand owners who do not register their brands, but sell in Indonesia through a distributor agreement, contained in Article 78 of the brand law. But the weakness of the brand owner must prove itself in the trial of ownership of the brand, so that the owners of foreign brands should register their brands before signing a distribution agreement as a guarantee of the protection of their rights.